An Overview of Coastal Waste Sources in Indonesia: A Review - Pebriyanto Setiawan; Wa Janarian Rumbia (Journal of Epidemiology and Health Science, 2025)
Background: Waste is a byproduct of various human activities that can lead to environmental pollution, particularly in coastal areas. Improper waste management in coastal zones contributes to significant environmental degradation, affecting both public health and marine ecosystems. This literature review examines the sources of waste in coastal areas, including household waste, industrial waste, and tourism-related waste, and explores their impacts on coastal communities and ecosystems. Objective: This study aims to review scientific articles related to the sources of waste in coastal areas of Indonesia, focusing on identifying the dominant factors contributing to coastal waste pollution. Methods: A Systematic Literature Review (SLR) was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The literature search targeted articles published between 2016 and 2025, using the keyword "coastal area waste sources." Relevant articles were selected based on predetermined inclusion and exclusion criteria. Results: The review findings indicate that the low level of public awareness regarding the importance of waste management is a major contributor to coastal pollution in Indonesia. Improper disposal practices, driven by limited knowledge of waste impacts, lead to the accumulation of waste in coastal environments. The improper disposal of waste is closely linked to public health problems, with an increase in pollution-related diseases such as diarrhea and skin infections reported in several coastal communities. Conclusion: Addressing coastal waste pollution requires a comprehensive approach involving community education, the provision of adequate waste management facilities, and the enforcement of environmental regulations. Implementing these strategies is expected to improve public health outcomes and support the sustainability of coastal ecosystems in Indonesia. Keywords: Waste, Coastal Areas, Public Health, Waste Management, Indonesia